Dinamika Perumusan Kebijakan Publik dalam Pembangunan Infrastruktur Jalan - Syaiful Hasan; Wahyu Satriyo Pamungkas; Dani Wahyu Pratama; Muhammad Mughni Labib (Idarotuna : Journal of Administrative Science, 2025)
Road infrastructure development in villages is a form of public policy that plays a strategic role in improving accessibility, economic growth, and the welfare of rural communities. However, the process of formulating village road development policies is inseparable from various dynamics involving the interests of actors, limited resources, and the socio-political conditions of the local community. This study aims to analyze the dynamics of public policy formulation in road infrastructure development in villages. The method used is a qualitative descriptive approach with data collection techniques through literature studies, observation, and documentation. The results of the discussion indicate that the dynamics of policy formulation are influenced by the process of identifying community needs, public participation in village deliberations, the role of the village government and the Village Consultative Body, and the influence of regional and central government policies. In addition, budget limitations and differences in interests among residents are major challenges in determining development priorities. The conclusion of this discussion confirms that participatory, transparent, and accountable formulation of village road development policies will produce more targeted and sustainable policies, thereby encouraging equitable village development.